Associated Factors with Dietary Adherence among People with Cardiovascular Metabolic Risk Factors based on PRECEDE Framework: a Mixed-Method Study - Leila Sabzmakan; Tahereh Kamalikhah; Mosharafeh Chaleshgar Kordasiabi; Mojgan Nourian (Hamadan University of Medical Sciences, 2021)
Aims: Difficulty in adhering to the recommended diet is a common problem among most people with metabolic risk factors of cardiovascular diseases. The purpose of this study was to identify factors associated with dietary adherence among people with metabolic risk factors based on a psychological theory. Materials & Methods: This research was a mixed-method study. In the qualitative phase, 50 people who had at least one metabolic risk factor and were referred to the diabetes units of Karaj health centers were interviewed, and the interviews were analyzed using NVivo10. In the quantitative phase, a survey was carried out to investigate factors associated with dietary adherence. The data were analyzed using structural equation modeling via AMOS18. Findings: Personal factors especially perceived self-efficacy (β=0.49; p=0.001) and perceived barriers (β=-0.33; p=0.001), were the most important predictors influencing dietary adherence. However, the findings of interviews and surveys were not aligned with structural and social factors. The structural factor was perceived as a deep factor influencing healthy eating behaviors in the qualitative phase, but the social factor was a significant predictor in the quantitative phase (β=0.67; p=0.001). Conclusion: Only 51.07% of people with at least one cardiovascular metabolic risk factor adheres to healthy eating behaviors. Although personal determinants are the most dominant contributors of dietary adherence among people with cardiovascular metabolic risk factors, social and structural factors should be considered to enhance dietary adherence.